A mendelian randomization study with populations of European ancestry rules out a causal relationship between inflammatory bowel disease and colorectal cancer - Li, Fan; Liu, Yuyuan; Wang, Zhaodi; Zhao, Qi; Li, Yuqin; Tang, Tongyu (Frontiers in Genetics, 2022)
Background: Ulcerative colitis (UC), a subtype of inflammatory bowel disease (IBD), has been found to be associated with colorectal cancer (CRC) in observational studies, but there is no evidence to support a causal relationship or reverse causality between the two. Methods: We employed two-sample bidirectional Mendelian randomization to estimate an unconfounded bidirectional causal relationship between IBD (including UC and Crohn's disease (CD)) and colorectal cancer. After searching IEU GWAS database and filtering SNPs, we applied a variety of MR methods including IVW method using qualified instrumental variables, and conducted sensitivity analysis to detect the heterogeneity and pleiotropy of instrumental variables. Results: After using three groups of SNPs (CD: 106, UC: 113, IBD: 70), the IVW method MR analysis showed that the results were not significant (result for UC: odds ratio (OR) [95% Confidence Interval (CI)]: 0.9998 [0.9991-1.0005], P value: 0.58; result for CD: OR [95%CI]: 0.99962 [0.99912-1.00012], P value: 0.14; results for IBD: OR [95%CI]: 0.99959 [0.99869 - 1.00048], P value: 0.36). MR-Egger regression, WM method and MR-RAPS method reached the same conclusion. Sensitivity analysis did not reveal heterogeneity and pleiotropy. Bidirectional MR analysis was performed using the same procedure, and the results of IVW MR analysis were also not significant (result for CD: OR [95%CI]: 1.07985 [0.00049 -2372.38304], P value 0.98; result for UC: OR [95%CI]: 0.27117 [0.00014-528.3707], P value: 0.74; result for IBD : OR [95%CI]: 0.47101 [0.0001-2242.94159], P value: 0.86). MR-Egger regression, WM method and MR-RAPS method also reached the same conclusion. Sensitivity analysis did not find any evidence of heterogeneity and pleiotropy. Conclusion: Contrary to the conclusions of previous observational studies, a two-sample MR analysis did not find a causal relationship or reverse causal relationship between IBD and CRC. Sporadic CRC (sCRC) may differ in pathogenesis from IBD-related CRC.